ANALISIS PERJANJIAN JUAL BELI DI FACEBOOK PONTIANAK INFORMASI PERSPEKTIF DEWAN SYARIAH NASIONAL MAJELIS ULAMA INDONESIA NO: 75/DSN/MUI/VII/2009 - Hadromi, Imam; Syahbudi, Syahbudi; Rahmiani, Nur (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2023)
The purpose of this research is to determine the buying and selling transactions, especially regarding mobile phones, carried out by sellers and buyers on Facebook Pontianak Informasi, considering the discovery of fraud issues therein. This study uses a qualitative method with a normative legal research type. The main data sources include interviews with the admin of Pontianak Informasi, sellers, and buyers. Meanwhile, secondary data used include primary legal materials such as the Fatwa of DSN-MUI No: 75/DSN MUI/VII/2009 and other materials such as books, journals, theses, and articles. The data collection techniques employed are interviews and documentation. Data analysis used a descriptive-qualitative approach through a series of activities including data collection, data reduction, data presentation, and conclusion drawing. The research findings indicate the following: 1) Buying and selling on Facebook Pontianak Informasi serves as a means for the Pontianak community and the surrounding area to carry out transactions with ease and competitive prices compared to other marketplaces. 2) Pontianak Informasi has a buying and selling mechanism through online advertisements and searching for information related to the transaction process. 3) The DSN-MUI Fatwa cannot be used absolutely to judge all transactions that take place on Facebook Pontianak Informasi because not all sellers violate this fatwa.